2012
DOI: 10.1159/000337136
|View full text |Cite
|
Sign up to set email alerts
|

Gantrez AN Nanoparticles for Ocular Delivery of Memantine: In vitro Release Evaluation in Albino Rabbits

Abstract: Aim: To prepare and evaluate the in vitro release of memantine-loaded poly(anhydride) (Gantrez®) nanoparticles (NPs). The clinical safety and retinal toxicity caused by unloaded NPs after sub-Tenon and intravitreal ocular injections were also evaluated. Methods: Preparation and characterization of this type of NP as well as the in vitro release study are described. Twenty-three healthy New Zealand rabbits were used for clinical and histological assessment after sub-Tenon and intravitreal ocular injections of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
0
11
0
1
Order By: Relevance
“…Other groups have previously formulated memantine into nanoparticles. Prieto and colleagues developed Gantrez, a memantine‐loaded poly(anhydride) nanoparticle formulation which possessed a similar diameter as our formulation but only contained 0.055 mg of memantine per mg of nanoparticles . While the authors demonstrated sustained release of memantine from these formulations after subtenon and intravitreal injection in the rabbit, the authors did not investigate topical administration.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Other groups have previously formulated memantine into nanoparticles. Prieto and colleagues developed Gantrez, a memantine‐loaded poly(anhydride) nanoparticle formulation which possessed a similar diameter as our formulation but only contained 0.055 mg of memantine per mg of nanoparticles . While the authors demonstrated sustained release of memantine from these formulations after subtenon and intravitreal injection in the rabbit, the authors did not investigate topical administration.…”
Section: Discussionmentioning
confidence: 97%
“…A key challenge for MEM in glaucoma is the development of a safe and effective means of long‐lasting delivery of MEM to the back of the eye . Incorporation of MEM into a nanoparticle drug delivery systems could provide a strategy to enhance the efficacy of this agent by increasing concentrations in target retinal tissues whilst reducing the risk of side effects associated with systemic dosing regimens .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the poly(vinyl ethers), poly(methyl vinyl ether) is a special case because it belongs to the class of thermo‐responsive polymers and exhibits a lower critical solution temperature (LCST) around 36 °C . Copolymers of MVE with maleic anhydride are widely used in medicine and pharmacology, in paper and textile industries, for manufacture of cosmetics and toiletry, as bioadhesives for drug delivery options and components of cellulosic biocomposites . Besides, these copolymers form interpolymer complexes possessing valuable properties …”
Section: Introductionmentioning
confidence: 99%
“…58 A separate study using polyanhydride nanoparticles to deliver mamantine into the eye showed that nanoparticles sustained drug release for 15 days following an initial burst release. 59 This suggests that drug therapy using these types of nanocarriers allows for extended, continuous release of the drug, which overcomes another obstacle facing conventional treatment options. In another study, 20-nm gold nanoparticles (Au-NPs) were able to pass through the blood-retinal barrier and associate with retinal-epithelial cells, retinoblastoma cells, and astrocytes without any observed toxicity.…”
Section: Nanotechnology Drugs and Targetingmentioning
confidence: 99%